(untitled) (Proceedings of the International Conference on Public Health, 2017)
Background: Cervical Cancer is the number one of woman killer in Indonesia. Each year, there are 20.928 new cervical cancer new cases in Indonesia. In 2012, there are 747 women in Malang suffering from cervical cancer. Early detection and pre-cervical cancer treatment are necessary to be the priority. One of the methods to distribute the information on early detection is by conducting the health promotion about cervical cancer and pap smear. Purpose: Knowing the health promotion effect on women knowledge level about cervical cancer and pap smear in public health center Kendal Kerep Malang city. Method: This study used quasi experimental one group pretest-posttest design. There 53 respondents were taken in total sampling. The respondents were given the pretest questionnaires followed by health consultation and Leaflet, afterwards, the respondents were given the posttest questionnaires. Data analysis was performed using paired t-test. Results: The result of paired t-test showed the value of P questionnaire of 0.000 so it is obtained P value <0,05 indicating that there was difference of influence of health promotion to woman knowledge level about Cervical Cancer and Pap Smear before and after counseling. Conclusion: There are health promotion effect on women knowledge level on cervical cancer and pap smear in public health center Kendal Kerep Malang city.